Sensing underground activity: diel digging activity pattern during nest escape by sea turtle hatchlings. (July 2021) - Nishizawa, Hideaki; Hashimoto, Yuichiro; Rusli, Mohd Uzair; Ichikawa, Kotaro; Joseph, Juanita
Abstract : Synchronous digging activity and emergence from underground nests is important for sea turtle hatchlings, as it reduces predation risk and decreases energy consumption. However, patterns of underground hatching and diel digging activity prior to emergence are invisible and remain largely unknown. In this study, we acoustically monitored the activity of green turtle, Chelonia mydas, hatchlings from hatching to emergence in the field and laboratory. During the hatching period, we did not observe characteristic acoustic events corresponding to pipping and hatching. Hatchlings started digging even though there were still unhatched eggs above them, indicating that green turtles did not hatch as one synchronous group. This observation did not support our hypothesis that synchronized hatching facilitates synchronous emergence. Digging activity tended to increase at night as the hatchlings approached the sand surface and nest emergence became imminent. It is not surprising that there was diel variation in digging activity as the hatchlings approached the surface because diel fluctuations in sand temperature can provide a diel cue. Surprisingly, a diel change in digging activity was also observed when hatchlings were still at a sand depth where temperature remained relatively constant throughout the day (that is, a few days before emergence) and in the laboratory at a constant temperature. This study suggests that the diel activity pattern of hatchling green turtles may occur even in the absence of a diel temperature fluctuation cue. Highlights: Green turtle hatchlings did not hatch synchronously. Digging activity occurred even when some eggs of the nest were unhatched. Synchronous digging increased at night as the emergence became imminent. Diel change in activity occurred even under constant conditions. Acoustic monitoring is useful for investigating underground animal behaviour.